2020 mPINC Scores: Opportunities for Improvement. Issue 2 (March 2022) - Spatz, Diane L.
Abstract : The Centers for Disease Control and Prevention surveys birthing hospitals in the United States every year about various aspects of their breastfeeding practices. Results from the Maternity Practice in Infant Nutrition and Care (mPINC) survey conducted in 2020 are now available. Our breastfeeding expert, Dr. Spatz, presents a summary of the results and offers suggestions on how nurse leaders in birthing hospitals can do better in aligning their practices with the evidence on interventions to ensure a robust milk supply and promote breastfeeding.